Fundamentals of Renal Pathology - Agnes B. Fogo, Arthur H. Cohen, , Arthur H. Cohen, J. Charles Jennette, Jan A. Bruijn, Robert B. Colvin (springer.com, 2006)
Section I: Renal Anatomy and Basic Concepts and Methods in Renal Pathology 1. Renal Anatomy and Basic Concepts and Methods in Renal Pathology Arthur H. Cohen Section II: Glomerular Diseases with Nephrotic Syndrome Presentations 2. Membranous Glomerulopathy Jan A. Bruijn 3. Membranoproliferative Glomerulonephritis Agnes B. Fogo 4. Minimal Change Disease and Focal SegmentalGlomerulosclerosis Agnes B. Fogo Section III: Glomerular Disease with Nephritic Syndrome Presentations 5. Postinfectious Glomerulonephritis Jan A. Bruijn 6. Immunoglobulin A Nephropathy and Henoch-SchÃ¶nlein Purpura J. Charles Jennette 7. Thin Basement Membranes and Alportâ€™s Syndrome Agnes B. Fogo Section IV: Systemic Diseases Affecting the Kidney